The Relationship Between Childhood Trauma, Pathological Dissociation, and Behavioral Addictions in Young Adults: Findings from a Cross-Sectional Study. Issue 3 (27th May 2023) - Imperatori, Claudio; Barchielli, Benedetta; Corazza, Ornella; Carbone, Giuseppe Alessio; Prevete, Elisabeth; Montaldo, Simone; De Rossi, Elena; Massullo, Chiara; Tarsitani, Lorenzo; Ferracuti, Stefano; Pasquini, Massimo; Biondi, Massimo; et al.
ABSTRACT: Interactions between childhood trauma (CT) and dissociation can contribute to psychiatric disturbances. We explored this phenomenon in relation to behavioral addictions (BAs) in a sample ( n  = 633) of young adults (age: 18–34 years). Self-report measures investigating CT, dissociation, and symptoms related to gambling disorder, internet gaming disorder, problematic social media use, exercise dependence and compulsive buying were used. Scales related to BAs were summarized into a single measure ("Total Behavioral Addiction Index" – TBAI) for inferential analyses. A model analyzing the direct and indirect effects of CT on TBAI through the mediation of pathological dissociation was performed, controlling for confounding factors. Measures on CT, dissociation, and TBAI were significantly associated with each other (all p  < .001). The total effect of CT on TBAI was significant (B = 0.063; CI: 0.045; 0.081); pathological dissociation significantly mediated such association (B = 0.023; CI: 0.013; 0.036). Our findings support the possibility that the interaction between CT and dissociation contributes to increase disturbances related to BAs.